Confirmatory Structural Model of a Collaborative Network in Central Mexico During the COVID-19 Era - Lirios, Cruz (Journal of Interdisciplinary Studies in Education, 2022)
The objective of this work was to confirm the factorial structure of collaborative networks in a university in central Mexico during the pandemic. A cross-sectional, psychometric, and confirmatory study was carried out with a sample of 300 administrators, teachers, and students from a public university in central Mexico. From a structural model, the results show that there is a dependent relationship between organizational climate and collaboration. Based on these findings, research lines related to trust as a determinant of knowledge networks and organizational collaboration.